Clomiphene citrate effect in obese men with low serum testosterone treated with metformin due to dysmetabolic disorders: A randomized, double-blind, placebo-controlled study. - Carla Pelusi; Vito Angelo Giagulli; Margherita Baccini; Flaminia Fanelli; Marco Mezzullo; Alessia Fazzini; Nicola Bianchi; Matteo Domenico Carbone; Giovanni De Pergola; Marianna Mastroroberto; Antonio Maria Morselli Labate; Renato Pasquali (PLoS ONE)
Context Low testosterone (T) levels are often found in obese men with impaired glucose tolerance (IGT) and overt type 2 diabetes (T2DM); however, the mechanisms underlying this condition and its correct therapy are still under debate. Objective To evaluate the effectiveness of clomiphene citrate (CC) in increasing endogenous T levels in obese men with low serum T and with IGT or T2DM treated with metformin (MET). Design Cross-over, randomized, double-blind, placebo-controlled study. Methods 24 obese men, aged 47.3 ±. 6.3 (range 35-55 years), with low T level (≤3 ng/mL) and naïve diagnosis of IGT or T2DM were included. Subjects were randomized to CC 25 mg/day or placebo (Plac) with MET 2 g/day for 3 months. After a 6-week wash-out period, subjects were moved to the alternative arm for additional 3 months. Clinical evaluation and blood exams performed prior to and at the end of treatment. Results Of 24 randomized, 21 were evaluable, classified as IGT (n = 11) or T2DM (n = 10). Compared to baseline levels, T levels increased significantly after 3 months of CC treatment (3.03±0.80 to 5.99±1.67 ng/mL P<0.001) but not after the Plac treatment (2.87±0.78 to 3.09±0.84 ng/mL P<0.001 between the treatments). T changes were similar in IGT and T2DM subjects. Gonadotropins as well raised significantly after CC treatment (LH 3.83±1.45 to 8.53±6.40 mU/mL; FSH 4.84±1.67 to 10.15±5.08 mU/mL P<0.001 respectively), whereas no changes for LH (3.51±1.59 to 3.63±1.39 mU/mL) but a smooth increased for FSH (4.61±2.49 to 5.39±2.65 mU/mL; P = 0.004) were shown after Plac treatment (LH P = 0.001 and FSH P = 0.002 between treatments). Furthermore, fasting glucose (106.8±23.2 to 101.1±25.7 mg/dL; P = 0.004), insulin (19.3±12.1 to 15.6±10.1 μU/mL; P = 0.010) and HOMA-IR (4.94±2.89 to 3.69±2.12; P = 0.001) decreased significantly during the CC treatment period, whereas no significant changes were observed in any of these parameters in the Plac treatment. Conclusions A low dose of CC therapy was able to significantly increase serum T levels in all participants with mild modifications of clinical and metabolic parameters. Trial registration EudraCT 2011-000439-10.